Development of High-Protein Cookies Enriched with Defatted Sacha Inchi (Plukenetia huayllabamana) Cake and Tarwi (Lupinus mutabilis Sweet) to Combat Child Malnutrition - Mateo Tapia; Nicolás Diez; Axel Sotelo; Rafael Alarcón; Nelson Tapia (Biology and Life Sciences Forum)
In Peru, 5 of every 10 children suffer from malnutrition, which increases the risk of developing non-communicable diseases (NCDs) at the early stages of their life. Sacha inchi (Plukenetia huayllabamana) cake is the by-product of the oil extraction process of the Amazon Peruvian seed and has high protein (56%) and fiber (5.9%) content. Tarwi (Lupinus mutabilis Sweet) is a Peruvian legume characterized by its high protein content (>50%) and high levels of tyrosine and tryptophan amino acids. Thus, the purpose of this research was to develop high-protein cookies enriched with defatted sacha inchi cake (DSIC) and defatted tarwi (DT) as an alternative snack to combat child malnutrition. Five types of cookies were developed, along with one control sample, containing corn flour (50% w/w), rice flour (20% w/w), and varying the content of quinoa flour, DSIC flour and DT flour (0, 10%, 30% w/w). The addition of DSIC and DT increased the content in protein from 12.13% to 20.30%, fat from 6.76% to 10.42%, and ash from 1.51% to 1.89% compared to the control sample. In contrast, the moisture content decreased from 10.21% to 10.78% and carbohydrates from 59.73% to 67.48%. Moreover, all cookies had high in vitro digestibility (70.91% to 74.17%) and relatively high antioxidant activity (346 to 469 μg GAE/g cookie) and phenolic content (1286 to 1755 μg trolox/g cookie). Sensory analysis showed that cookies enriched with DT were more appealing to the panelists than those enriched with DSIC and the control sample. Hence, these cookies could serve as a gluten-free nutritional food alternative to combat child malnutrition.